Benzylation of benzene and other aromatics by benzyl chloride over mesoporous AlSBA-15 catalysts - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hartmann, Martin; Halligudi, Shivappa B. (Microporous and Mesoporous Materials, 2005)
Aluminum-containing mesoporous molecular sieves AISBA-15 with different n(Si)/n(Al), ratios and AIMCM-41 have been synthesized hydrothermally and characterized in detail by physicochemical methods, viz. XRD, N(2) adsorption and (27)Al NMR spectroscopy. The low angle XRD and N2 adsorption measurements reveal that the structural order of SBA-15 was retained after the incorporation of Al. The increase of the unit cell parameter with increasing aluminum content and (27)Al MAS NMR spectroscopy confirm the incorporation of aluminum in the framework. Benzylation of benzene and substituted benzenes reaction employing benzyl chloride as the alkylating agent over AISBA-15 and AIMCM-41 have been investigated. The influence of various reaction parameters such as reaction temperature, reactant feed ratio and catalyst amount affecting the activity and selectivity of AISBA-15, have been studied. Among the mesoporous catalysts studied, AISBA-15(45), where the number in parentheses indicates the molar nsilnA, ratio, shows both high conversion and high selectivity for the benzylation of benzene. The activity of this catalyst for the benzylation of different aromatic compounds is in the following order: benzene > toluene > p-xylene > mesitylene > anisole. Kinetics of the benzene benzylation over different catalysts have also been investigated. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Alkylation; AlSBA-15; Benzylation; SBA-15

Zirconia-supported phosphotungstic acid as catalyst for alkylation of phenol with benzyl alcohol - Devassy, Biju M.; Shanbhag, G. V.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of phenol with benzyl alcohol was carried out using zirconia-supported phosphotungstic acid (PTA) as catalyst. The catalysts with different PTA loadings (5-20 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 650 to 850 degrees C) were prepared and characterized by (31)p MAS NMR and FT-IR pyridine adsorption spectroscopy. The catalyst with optimum PTA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents. 31p MAS NMR spectra of the catalysts showed two types of phosphorous species, one is the Keggin unit and the other is the decomposition product of PTA and the relative amount of each depends on PTA loading, calcination temperature and the solvent used for the catalyst preparation. The catalysts with 15% PTA on zirconia calcined at 750 degrees C showed the highest Bronsted acidity. At 130 degrees C and phenol/benzyl alcohol molar ratio of 2 (time, I h), the most active catalyst, 15% PTA calcined at 750 degrees C gave 98% benzyl alcohol conversion with 83% benzyl phenol selectivity. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Benzylation; phenol; Phosphotungstic acid; Zirconia

Benzylation of acetic acid to benzyl acetate over highly active and reusable micro/meso-HZSM-5 - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Raut, Sunil A.; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
Catalytic benzylation of acetic acid (AA) with benzyl alcohol (BA) to benzyl acetate was studied over zeolites viz. H-ZSM-5 (microporous, medium pore), Micro/Meso-HZSM-5 (combination of micro- and meso pore), H-Beta (microporous, large pore) to investigate catalytic activity and selectivity towards benzyl acetate. Micro/Meso-HZSM-5 obtained by desilication post-treatment has been employed as a heterogeneous catalyst for benzylation reaction probably for the first time. Micro/Meso-HZSM-5 was found to be a promising catalyst for benzylation with AA conversion of 94%, selectivity towards benzyl acetate of 95%. The detailed optimization of process parameters such as molar ratio, catalyst loading, reaction temperature and time was also presented. Micro/Meso-HZSM-5 catalyst was observed to be stable for six cycles (1 fresh and 5 recycles). The first order reaction kinetics (R-2 >0.98) indicated that reaction rate constants increased with increasing reaction temperature. The activation energy for benzylation of AA with BA over Micro/Meso-HZSM-5 was obtained to be 15.07 kJ mol(-1), which is far less than the reported. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acetic acid; Benzyl acetate; Benzyl alcohol; Benzylation; Micro/Meso-HZSM-5; Reaction kinetics